Characterization of individuals with cancer, residing in rural areas, practices in the use of pesticides and levels of erythrocyte acetylcholinesterase (Research, Society and Development, 2021)
The aim of the present study was to characterize individuals from rural areas, diagnosed with cancer, regarding the practices in the use of pesticides, physical, emotional symptoms, intoxication and levels of erythrocyte acetylcholinesterase. This is a cross-sectional, quantitative, descriptive study, in a general hospital, with 92 cancer patients and farmers. The project was approved by CEP under number 2,626,873. Data collection instrument with sociodemographic variables, practices in handling pesticides and measurement of erythrocyte acetylcholinesterase. Data analysis using the Statistical Package for Social Science program, descriptive and analytical statistics. The results showed that the majority of the male, elderly, had a low level of education. Small rural properties predominate, cultivation of fruits and vegetables. 63% occupationally exposed to pesticides; for protection, 56.8% wear boots, “always”. Insufficient technical guidance. Low frequency of intoxication. Lower average of erythrocyte acetylcholinesterase in the group exposed to active pesticides, statistically significant. There was a predominance of family farming, with the production of fruit and vegetables and the use of equipment that favors direct contact with pesticides, including the inappropriate use of PPE. Gaps regarding the safe use of these products, probably related to education, make them susceptible to aggravations of direct and indirect exposure. Measurement of erythrocyte acetylcholinesterase showed normal mean values ​​and requires complementary exams and continuous monitoring. Results refer to actions and educational interventions aimed at preventing diseases and reducing the growing rates of cancer in this population.